Justification for experimental methods for circuit training aerobics classes first mature age women - Martyniuk, O.V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: develop and validate a methodology for circuit training aerobics. Methodology focused on improving physical health first mature age women. Material : a study was conducted with 81 women (age 21 - 35 years). Results : justified the means and methods of circuit training, the duration of the structural components, the rational parameters of physical activity, pulse modes. Depending on the physical health of women developed a set of circuit training for the main part of the session. Complex circuit training consists of 2 series, active rest interval between 3 minutes. Duration of employment in one series of 23 minutes. Exercises are performed at 5 locations: 3 - aerobic (3x5 min), 2 - power (2x4 min). The total duration of training - 49 minutes. The intensity of the training load is regulated by the level of physical health and the maximum test results. Conclusions : The positive changes morphofunctional indicators show an increase in the body’s bioenergy and women transition to a higher level of physical health.